Vinca herbacea Extract Suppresses NF-kB Signaling and Modulates SIRT1/AMPK/PGC1α Axis to Exert Antidiabetic Effects in Streptozotocin- Induced Diabetic Rats - Nasim Abedimanesh; Morteza Nouri; Kosar Mohammadnejad; Maedeh Barati; Elham Dabardani; Elahe Kakavand; Mohammad Reza Eskandari; Seyed Hojjat Hosseini; Seyede Momeneh Mohammadi; Iraj Jafari Anarkooli; Maryam Noubarani; Sina Andalib; et al. (Iranian Society of Pharmacognosy, 2022)
Background and Objectives: AMPK/SIRT1/PGC1α signaling pathway has an important role in diabetic condition. Some natural products exert anti-diabetic effects by modulating this pathway and also by inhibition of NF-κB. Vinca herbacea has potent antioxidant and anti-inflammatory activities In the present study, we investigated the effects of this plant on the AMPK/SIRT1/PGC1α axis and NF-κB genes expression as well as glucose, insulin levels and total antioxidant capacity in streptozotocin- induced diabetic rats. Methods: Streptozotocin induced diabetic male Sprague-Dawley rats were assigned to six groups: control, diabetic, diabetic + different doses of Vinca herbacea extract (100, 200 and 400 mg/kg.b.w) and glibenclamide. Fasting blood glucose, serum insulin and total antioxidant capacity were measured. The histopathology of liver and pancreas were evaluated. Real-time PCR was performed to assess gene expression levels. Results: Vinca herbacea extract (100 and 200 mg/kg.b.w) significantly reduced fasting blood glucose and 2-h blood glucose and increased serum insulin levels and total antioxidant capacity compared to the control diabetic rats. Also an improvement in lipid profile and liver enzymes levels was observed. According to the histopathological assay, different damages induced by streptozotocin to liver and pancreas tissues were largely eliminated by treatment with the extract. Vinca herbacea extract significantly upregulated the AMPK, SIRT1 and PGC-1α and downregulated the NF-κB mRNA expression compared to the diabetic control rats. Conclusion: Anti-diabetic effects of V. herbacea extract were indicated in streptozotocin -induced diabetic rats. The AMPK/SIRT1/PGC1α/NF-κB signaling pathway was suggested as the mechanism involved in the protective effects of this extract in diabetes.